Respuesta :

Answer:

D) dy/dx > 0 and d²y/dx² > 0

Step-by-step explanation:

Use implicit differentiation to find dy/dx and d²y/dx².

x²y³ = 576

x² (3y² dy/dx) + (2x) y³ = 0

3x²y² dy/dx = -2xy³

3x dy/dx = -2y

dy/dx = -2y / (3x)

d²y/dx² = [ (3x) (-2 dy/dx) − (-2y) (3) ] / (3x)²

d²y/dx² = (-6x dy/dx + 6y) / (9x²)

d²y/dx² = (-6x (-2y / (3x)) + 6y) / (9x²)

d²y/dx² = (4y + 6y) / (9x²)

d²y/dx² = 10y / (9x²)

Evaluating each at (-3, 4):

dy/dx = -2(4) / (3(-3))

dy/dx = 8/9

d²y/dx² = 10(4) / (9(-3)²)

d²y/dx² = 40/81

Both are positive.

ACCESS MORE